Verify the following:
![( \frac{ - 3}{4} ) {}^{3} = \frac{27}{64} ( \frac{ - 3}{4} ) {}^{3} = \frac{27}{64}](https://tex.z-dn.net/?f=%28+%5Cfrac%7B+-+3%7D%7B4%7D+%29+%7B%7D%5E%7B3%7D++%3D+++%5Cfrac%7B27%7D%7B64%7D+)
Answers
Answered by
1
Answer: therefore, 3×3×3= 27 and 4×4×4 = 64. hence the answer is 3/4. Step -by-step explanation: Hope it helps!! pls mark ...
Similar questions
Computer Science,
2 months ago
Computer Science,
2 months ago
History,
2 months ago
Math,
3 months ago
English,
3 months ago
Physics,
11 months ago
English,
11 months ago